FACTORS RELATED TO THE USE OF PERSONAL PROTECTION EQUIPMENT (PPE) FOR NURSE SAFETY AT GRANDMED HOSPITAL IGD IN 2022 - Risky Yulanda; Rahmad Gurusinga (JURNAL KESMAS DAN GIZI (JKG), 2022)
Infection prevention and control efforts carried out by nurses and medical personnel are through recommendations for the use of Personal Protective Equipment (PPE) worn at work. The use of PPE is a method in the final phase in controlling accidents and diseases due to work impacts. However, the use of PPE will be very critical if the control has been carried out optimally but the potential risks are still classified as vulnerable. This study aims to analyze the use of personal protective equipment in maintaining patient safety in the ER Grandmed Lubuk Pakam Hospital including: knowledge, attitudes, education, and years of service at Grandmed Hospital. This research was conducted quantitatively with the method used was a survey with a Cross Sectional Study approach. The results of this study are that there is a relationship between knowledge and the use of PPE on patient safety, there is a relationship between Attitude and the use of PPE for patient safety, there is a relationship between education and the use of PPE for patient safety and there is a relationship between years of service and the use of personal protective equipment for patient safety.